2011
DOI: 10.1097/nmd.0b013e318229cf90
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Cross-Sectional Study on the Information About Schizophrenia Divulged by a Prestigious Daily Newspaper

Abstract: Media is an important source of information about mental health for the public. The current study analyzed the information about schizophrenia divulged by the largest Brazilian newspaper. A content analysis examined articles on health and news involving affected individuals or suspected cases. The articles were rated against indicators of poor quality reporting and of effective health communication. The presence of myths was examined. The search identified 687 articles, 75 of which fulfilled the inclusion/excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The independent impact of perceived dangerousness as a very important mediator of stigma has been stressed by various authors (Link et al 1999;Martin et al 2000). However, one must also note that such effects of labelling are undoubtedly shaped and biased through the influence of the media (Dubugras et al 2011) or by socio-cultural characteristics (Abdullah & Brown, 2011;Hengartner et al 2012). Stigma is per definition deeply embedded and entrenched with different socio-cultural characteristics, beliefs and values.…”
Section: Discussionmentioning
confidence: 99%
“…The independent impact of perceived dangerousness as a very important mediator of stigma has been stressed by various authors (Link et al 1999;Martin et al 2000). However, one must also note that such effects of labelling are undoubtedly shaped and biased through the influence of the media (Dubugras et al 2011) or by socio-cultural characteristics (Abdullah & Brown, 2011;Hengartner et al 2012). Stigma is per definition deeply embedded and entrenched with different socio-cultural characteristics, beliefs and values.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that concern exists for inaccurate information and portrayal of negative image of mental illness in the media (20-23). A Canadian study investigated information provided by web sites on treatment of schizophrenia and attention deficit hyperactivity disorder and found that the quality was generally poor and misleading (24).…”
Section: Introductionmentioning
confidence: 99%
“…However, the content of articles dealing with this illness has not been a subject of scientific investigation. Most studies involved mental disorder in general, violence by the individuals with the serious mental illness, or schizophrenia (20, 21, 25). We were interested to find out whether the number of articles describing PTSD in the Korean print media continues to grow and how accurately and appropriately the newspapers report the cause, the symptoms and treatment of PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Such articles are published at a higher rate than that for physical illness. 8 Of these, schizophrenia and psychosis are focused on stigmatization from mass media articles, [9][10][11][12] and had the highest rate of negative contexts compared with other psychiatric diseases. 9,11 As schizophrenia is thought to be one of the most stigmatized diseases compared with physical and psychiatric diseases, more appropriate information along with positive and recovery-oriented impressions through mass media are mandatory to promote early detection and care for young people suffering from schizophrenia and psychosis.…”
Section: Introductionmentioning
confidence: 99%